Use of poly(methyl methacrylate) with an unsaturated chain end as a macroinitiator precursor in organocatalyzed living radical block polymerization - Chang, Jun Jie (2020)
Poly(methyl methacrylate) (PMMA) with an unsaturated chain end (PMMA–Y) was transformed into PMMA–iodide (PMMA–I) in situ in the organocatalyzed living radical polymerization of butyl acrylate; the generated PMMA–I acted as a macroinitiator to successfully generate a PMMA–PBA–I block copolymer, where PBA is poly(butyl acrylate). The use of PMMA–Y overcomes the drawback of the direct use of the isolated PMMA–I, i.e. its general lack of long-term stability upon storage, and thus significantly improves the ease of operation. This method is highly suitable for practical use. A quantitative mechanistic study on the transformation of PMMA–Y into PMMA–I was also conducted.